An optimal design of thermal protection based on materials morphology - Salosina, Margarita O.; Alifanov, Oleg M.; Nenarokomov, Aleksey V. (Computer Assisted Methods in Engineering and Science, 2019)
The paper presents a methodology for the optimal design of multilayer thermal protection based on high-porosity open-cell foam, taking into account the foam morphology. The vector of design parameters includes the thicknesses of layers, porosity and cell diameter of open-cell foam and should ensure required operation temperature on the boundaries of layers and a minimum of the total mass of the system. The optimization problem is solved using a computational scheme, which combines the projected Lagrangian method with the quadratic subproblem and the penalty function method. The penalty function method provides a good initial estimate of the optimal parameters’ values for the projected Lagrangian method with excellent local convergence properties. To illustrate the implementation of the developed algorithm and the corresponding software, the problem of choosing the optimal layer thicknesses for the multilayer thermal protection of a spacecraft along with the cell diameter and porosity of foam is considered.